UPAYA PENINGKATAN HASIL BELAJAR MAHASISWA MELALUI PENERAPAN PROBLEM BASED LEARNING PADA MATA KULIAH FISIKA TEKNIK - Erni Mariana; Sulis Anjarwati; Nurkaif; Ahmad Hairuji (STKIP Subang, 2026)
This course has long been considered by students to be quite intimidating. This is because the material is mostly calculation-based. For students with low quantitative abilities, this course becomes uninteresting. As a result, student learning outcomes in this course are low. Based on the results of the analysis of student answer patterns, it is clear that most students are able to answer theoretical questions. However, for applied questions, most students are unable to answer correctly. This indicates that student abilities are still at a purely theoretical level, while students' ability to apply the theoretical concepts they receive is still lacking. Data collection techniques used in this study were documentation, tests, and observations. This study is a classroom action research by exploring problems that occur in students' classes and then identifying these problems to find the main problems in learning. After the main problems in learning are identified, the appropriate method or approach is determined to overcome these problems. The results of the study indicate that the application of the Problem Based Learning (PBL) model in Engineering Physics courses can improve student learning outcomes. This improvement is evident in the increase in students' average grades in each learning cycle and the increase in the percentage of learning completion. In addition, student learning activities have also increased, as indicated by student activity in discussions, expressing opinions, and students' ability to solve problems related to Engineering Physics material.